Dhundhunan: Asimilasi Budaya dan Pergeseran Nilai - Agus Fakhrina (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
This research explores the assimilation of Islamic culture in Javanese culture in dhundhunan ceremony that is performed in Javanese moslem community living in Karangjompo, Tirto, Pekalongan, Central Java and the value changes in that ceremony. To achieve the aim of this research, observation and interview were done. It was found that there were some assimilations and value changes in that ceremony, i.e. prayers that were performed in that ceremony adopted Islamic culture like asking God for safety by reciting shalawat barzanji. Meaning of the symbols uborampe in that ceremony has been forgotten by them. They perform that ceremony only formally without caring about the meaning and feeling the magic values.